Marketing communication policy in the management system of innovative development of enterprises - Illiashenko, Sergii (My University, 2021)
The obtained results deepen foundations of innovative management in terms of development of methodology of formation of marketing communication policy of the main types of innovative development strategies of an enterprise.

Отримані результати розвивають засади інноваційного менеджменту у частині поглиблення і розвитку методологічних засад формування маркетингової комунікативної політики основних типів стратегій інноваційного розвитку підприємства.
Маркетингова комунікаційна політика в системі управління інноваційним розвитком підприємств
Keywords: marketing of innovations; communication policy; innovative development; enterprise management; маркетинг інновацій; комунікаційна політика; інноваційний розвиток; управління підприємством